Targeting FGFR2 with alofanib (RPT835) shows potent activity in tumour models. (July 2016) - Tsimafeyeu, Ilya; Ludes-Meyers, John; Stepanova, Evgenia; Daeyaert, Frits; Khochenkov, Dmitry; Joose, Jean-Baptiste; Solomko, Eliso; Van Akene, Koen; Peretolchina, Nina; Yin, Wei; Ryabaya, Oxana; Byakhov, Mikhail; et al.
Abstract: Alofanib (RPT835) is a novel selective allosteric inhibitor of fibroblast growth factor receptor 2 (FGFR2). We showed previously that alofanib could bind to the extracellular domain of FGFR2 and has an inhibitory effect on FGF2-induced phoshphorylation of FRS2α. In the present study, we further showed that alofanib inhibited phosphorylation of FRS2α with the half maximal inhibitory concentration (IC50) values of 7 and 9 nmol/l in cancer cells expressing different FGFR2 isoforms. In a panel of four cell lines representing several tumour types (triple-negative breast cancer, melanoma, and ovarian cancer), alofanib inhibited FGF-mediated proliferation with 50% growth inhibition (GI50) values of 16–370 nmol/l. Alofanib dose dependently inhibited the proliferation and migration of human and mouse endothelial cells (GI50 11–58 nmol/l) compared with brivanib and bevacizumab. Treatment with alofanib ablated experimental FGF-induced angiogenesis in vivo . In a FGFR-driven human tumour xenograft model, oral administration of alofanib was well tolerated and resulted in potent antitumour activity. Importantly, alofanib was effective in FGFR2-expressing models. These results show that alofanib is a potent FGFR2 inhibitor and provide strong rationale for its evaluation in patients with FGFR2-driven cancers. Highlights: The recent identification of fibroblast growth factor receptor 2 (FGFR2) in different cancer types has generated an opportunity for a novel target-based therapy. Alofanib is a small-molecule selective FGFR2 inhibitor with allosteric properties. Inhibition of FGFR2 has potent in vitro effects on FGFR2-mediated cancer cell proliferation and apoptosis. Inhibition of FGFR2 affects endothelial and cancer cell proliferation, migration and mature vessel formation. The mechanism of in vivo growth inhibition by alofanib is FGFR2 dependent.